2020
DOI: 10.1038/s41598-020-59396-3
|View full text |Cite
|
Sign up to set email alerts
|

A novel vibriophage exhibits inhibitory activity against host protein synthesis machinery

Abstract: Since the emergence of deadly pathogens and multidrug-resistant bacteria at an alarmingly increased rate, bacteriophages have been developed as a controlling bioagent to prevent the spread of pathogenic bacteria. One of these pathogens, disease-causing Vibrio parahaemolyticus (Vp AHPND ) which induces acute hepatopancreatic necrosis, is considered one of the deadliest shrimp pathogens, and has recently become resistant to various classes of antibiotics. Here, we discovered a novel vibriophage that specifically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 76 publications
0
15
0
Order By: Relevance
“…The supernatant was serially diluted in SM buffer, and a spot titer test was performed to determine the number of free phage particles in the supernatant. The experiment was performed in triplicates ( Thammatinna et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…The supernatant was serially diluted in SM buffer, and a spot titer test was performed to determine the number of free phage particles in the supernatant. The experiment was performed in triplicates ( Thammatinna et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…To observe the progress of the replication cycle of the phage Callisto in comparison to the well-studied chimalliviruses PhiKZ, we performed a single-cell infection assay and observed DAPI-staining DNA to follow the phage reproduction process in the host cells. 41 , 52 The results showed that, during the phage infections, the infected Pseudomonas cells had their morphology altered throughout the time, which might be a result of the phage infections compared to the uninfected cell control ( Figures 3 A, 3C, and 3D). During infection with phage PhiKZ ( Figure 3 A; PhiKZ), the phage assembled the phage nucleus localized close to the midcell of the host ( Figure 3 A; PhiKZ, green arrows).…”
Section: Resultsmentioning
confidence: 98%
“…Two genes (ORFs 8 and 13) were predicted to encode virions and phage structure proteins. Major capsid protein (ORF 9) and minor capsid protein (ORF 11) were identified in the genome; the former is the major structural component of icosahedral virus particles, and the latter is believed to enhance the stability of capsid structure by forming protein–protein interactions (Thammatinna et al, 2020 ). Four ORFs were related to tube structure, including major tail tube protein (ORF 17), which is used for viral genome delivery to the host cells (Davidson et al, 2012 ); tail fiber protein (ORF 25), which is responsible for host-range determination (Garcia-Doval and van Raaij, 2012 ); and two tail proteins (ORFs 24 and 26).…”
Section: Resultsmentioning
confidence: 99%